Rasch Meta-Metres of Growth for Some Intelligence and Attainment Tests - Andrich, David; Marais, Ida.; Sappl, Sonia (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book adapts Rasch's approach for quantifying growth on physiological variables, where growth decelerates, to intellectual variables. To apply this approach, it is necessary to construct measurements in a constant unit over the relevant range of the variable. With such measurements, the book illustrates the approach to quantifying growth on six intellectual variables - two intelligences tests and two each of tests of proficiencies in reading comprehension and mathematics. The book discusses how it is not immediately obvious that deceleration on a quantitative scale should also hold for the growth in intellectual variables. It goes on to show that this is indeed the case with all six tests analysed and considers some implications of this feature for understanding intellectual development, in particular the centrality of the growth trajectory set in early life. .
Measurement and the study of growth -- Probabilistic fundamental measurement and invariance -- The formulation of a meta-metre in which growth is linear -- Estimates of the rate of growth and initial status -- Application of the modified meta-metre to physical growth -- Growth on the Stanford-Binet test of general intelligence,- Growth in reading and mathematics achievement: ECLS-K study -- Growth in reading and mathematics achievement: NLSY study -- Further examples of growth in reading and mathematics achievement -- Decelerating growth and the setting of an early trajectory -- Summary and discussion.
Keywords: Educational tests and measurements; Learning, Psychology of; Educational psychology; Mathematics; Assessment and Testing; Instructional Theory; Educational Psychology; Mathematics Education